De quelle nostalgie l’utopie andalouse d’Aragon est-elle le miroir ? - Stéphane Baquey (Conserveries Mémorielles)
Le Fou d’Elsa, a narrative poem published by Louis Aragon in 1963, tells the story of the end of the emirate of Granada in 1492. The representation of a dreamed Andalusia allows the writer, who is also a communist leader and ideologue, to deliver an indirect speech about the history of his time, mainly about the consequences of the 20th Congress of the Communist Party of the Soviet Union and about the Algerian War. This strategy of allusive speech leads the study to try to find out the contextual relevance of the poem on the basis of a collation of different speech genres, between the poem itself and other Aragon’s public utterances. Thus, in Le Fou d’Elsa, the strategy of allusive speech allows shifts which re-qualify the status of utopia and nostalgia in a speech unleashed form orthodox communism. This nostalgia of what could have happened, being dislocated in the culture of the Muslim worlds, also leads to reconceive the claims of a universalism which would not take into account as a prerequisite a principle of hospitality.